Conflict of Irish Cultural Identity in Brian Friel’s Translation - Ambar Andayani; Edi Pujo Basuki; Ali Mustofa (JENTERA: Jurnal Kajian Sastra, 2023)
This research purposes to analyze Irish cultural identity conflict in Brian Friel’s Translation, namely by analyzing why it happens and how it impacts to Irish. The method applied to analyze is descriptive qualitative method by doing content analysis through data collecting technique in the form of library research. From the data source of Brian Friel’s Translation, the researcher does the technique of interpretation by using Homi K. Bhabha’s postcolonialism theory of mimicry concept to identify the conflict of Irish cultural identity found in the literary work. The result of the research shows that the setting in Brian Friel’s Translation is Northern Ireland in the 19th century. Irish people are surrendered to be the British colony. British people colonize Irish in various ways; destroying Irish rights by forcing them to work very hard on potato plantation in the area where they live to fulfill British people food, forbidding Irish to use their own language or do their Catholic religious worship, executing Ordnance survey namely by replacing names of local places in Northern Ireland for the importance of imperialism forcibly. That colonialism causes suffering, starving and poverty. Through the dialogues, it reflects that British people want to abolish Irish language and culture to replace it to British language and culture which is considered more modern. AbstrakPenelitian ini bertujuan menganalisis konflik identitas budaya bangsa Irlandia dalam drama Translation karangan Brian Friel, yaitu dengan mengupas mengapa konflik itu terjadi, dan bagaimana akibatnya terhadap bangsa Irlandia. Metode yang diterapkan adalah metode deskriptif kualitatif, dengan menganalisa isi melalui teknik pengumpulan data berupa studi kepustakaan. Dari sumber data drama Translation karangan Brian Friel, peneliti memakai teknik interpretasi melalui teori postkolonialisme konsep mimikri dari Homi K Bhabha untuk mengidentifikasi konflik identitas budaya bangsa Irlandia yang ditemukan pada karya sastra tersebut. Hasil penelitian menunjukkan bahwa seting yang terdapat pada drama tersebut adalah pedesaan Irlandia Utara pada abad 19. Bangsa Irlandia takluk menjadi koloni bangsa Inggris. Bangsa Inggris menjajah dengan berbagai cara, menghancurkan hak-hak bangsa Irlandia dengan memaksa mereka kerja paksa di perkebunan kentang tempat tinggal mereka untuk memenuhi kebutuhan makanan rakyat Inggris, melarang mereka menggunakan bahasa asli atau melakukan ibadah agama Katolik, dan melakukan survei Ordnance yaitu mengganti paksa nama-nama lokal di Irlandia utara ke bahasa Inggris untuk kepentingan imperialisme. Penjajahan tersebut menyebabkan penderitaan, kelaparan dan kemiskinan. Melalui dialog-dialognya tercermin bahwa bangsa Inggris ingin melenyapkan budaya serta bahasa Irlandia, lalu menggantinya dengan budaya dan bahasa Inggris yang dianggap lebih modern.